Development of photo-crosslinkable platelet lysate-based hydrogels for 3D printing and tissue engineering. (16th August 2021) - Min, Sung Jun; Lee, Jae Seo; Nah, Haram; Kim, Seung Hyeon; Moon, Ho-Jin; Reis, Rui L; Kwon, Il Keun; Heo, Dong Nyoung
Abstract: Three-dimensional (3D) printing shows potential for use as an advanced technology for forming biomimetic tissue and other complex structures. However, there are limits and restrictions on selection of conventional bioinks. Here we report the first 3D-printable platelet lysate (PLMA)-based hydrogel, which consists of platelet lysate from whole blood of humans that can simulate the 3D structure of tissues and can be formed into a crosslinked hydrogel layer-by-layer to build cell-laden hydrogel constructs through methacrylated photo-polymerization. Furthermore, it can be customized for use with various tissues by controlling the physical properties according to irradiation time and concentration. In particular, different cells can be mixed and printed, and the integrity of the 3D printed structure can maintain its shape after crosslinking. The bio-ink exhibits excellent cell diffusion and proliferation at low concentrations, which improves moldability and biocompatibility. The 3D-printable PLMA bioinks may constitute a new strategy to create customized microenvironments for the repair of various tissues in vivo using materials derived from the human body.